THE EFFECT OF THE BOOK OF TAQRIB-BASED MUDZAKARAH METHOD ON FIQH KNOWLEDGE AND PROPHETIC INTELLIGENCE - Ridwan Setiawan; Ilzamuddin Ma'mur; Khalid; Wasehudin; Fitri Hilmiyati (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Pesantren is one of the oldest educational institutions in Indonesia that has existed since before the establishment of public schools and madrasas. The purpose of this study is to determine the influence of the mudzakarah method on the book of Taqrib on fiqh knowledge and prophetic intelligence at the Riyadul 'Awamil and Luhur Al-Washathiyah Curug Islamic Boarding Schools in Serang City, Banten. This study uses a quantitative approach. The research model used is a true group control experimental design, because in this study the mudzakarah method is used as an experiment using a true group control experimental design. The results of this study are the first to cancel the pre-test scores of the control class and the experimental class at the Riyadul 'Awamil and Luhur Al-Washathiyah Islamic Boarding Schools of 62.75 and 63.17. Second, the average post-test scores of the control class and the experimental class at the Riyadul 'Awamil and Luhur Al-Washathiyah Islamic Boarding Schools were 76.75 and 77.08. Third, the average pre-test score of the control and experiment class at the Riyadul 'Awamil Islamic Boarding School was 62.75, and the post-test of the control and experimental class at the Riyadul 'Awamil Islamic Boarding School was 76.75 with an increase of 22.32 percent. Meanwhile, the average score after the control and experimental class test at the Riyadul 'Awamil Islamic Boarding School was 63.17, and after the control and experimental class test at the Riyadul 'Awamil Islamic Boarding School was 77.08 with an increase of 22.02 percent. Based on the test given by the researcher to get 50 valid questions because the significance value was less than 0.05, the test was declared reliable because the alpha value was greater than 0.60, the test was declared abnormal therefore the researcher conducted the Wilcoxon test and the test was declared influential because the significance value was less than 0.05.